Pragmatic Failures in Intercultural Communication: Evidence from Jordan - Абдель Рахман Алтахіне; Марва Абу Хашиш; Дана Хамайде (Психолінгвістика, 2024)
Aim. This paper investigates the pragmatic errors of Jordanian EFL learners from a cultural perspective on communication. It is suggested that pragmatics, or the study of how language is used in context, plays a crucial role in L2 learners’ communicative skills. Thus, the research aims to provide a comprehensive understanding of how the lack of pragmatic competence can lead to communication breakdowns and pragmatic failure. In this study, the researchers examine the pragmatic errors such as misunderstandings produced by these learners.